2008
DOI: 10.1007/s00586-008-0722-x
|View full text |Cite
|
Sign up to set email alerts
|

SAPHO syndrome associated spondylitis

Abstract: The concept of synovitis, acne, pustulosis, hyperostosis, osteitis (SAPHO) syndrome has been well clarified, after Chamot et al. suggested this peculiar disorder in 1987. The most commonly affected site in SAPHO syndrome is the anterior chest, followed by the spine. However, the clinical course and taxonomic concept of SAPHO spinal lesions are poorly understood. This study was performed to analyze: (1) the detailed clinical course of spinal lesions in SAPHO syndrome, and (2) the relationship between SAPHO synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 19 publications
(37 reference statements)
1
28
0
2
Order By: Relevance
“…Spondylitis may precede with a long interval of cutaneous and other bony lesions in which case the diagnosis may be difficult, explaining the frequent duration between the onset of symptoms and diagnosis. This is what occurred in the 13 cases reported by Tagigawa et al [32] in the October issue.…”
Section: Infection Following Instrumented Spinal Fusionsupporting
confidence: 57%
“…Spondylitis may precede with a long interval of cutaneous and other bony lesions in which case the diagnosis may be difficult, explaining the frequent duration between the onset of symptoms and diagnosis. This is what occurred in the 13 cases reported by Tagigawa et al [32] in the October issue.…”
Section: Infection Following Instrumented Spinal Fusionsupporting
confidence: 57%
“…Hukuda et al reported that 4.7% and 0.3% of Japanese 990 SNSA patients showed PPP and SAPHO syndrome, respectively (Hukuda et al, 2001). Takigawa et al reported that 23% of 13 SAPHO syndrome patients met the criteria of SNSA regardless of whether ESSG or Amor criteria were used (Takigawa et al, 2008). In their series, if PPP is added as a skin lesion to the criteria of spondyloarthropathy, 100% and 92% of their cases would fullfill the diagnostic criteria of ESSG and Amor, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Sonozaki proposed pustulotic arthro-osteitis is one subtype of SNSA (Sonozaki et al, 1981). Thus Takigawa et al proposed that SAPHO syndrome, especially spinal lesions related to PPP, should be recognized as a subtype of SNSA (Takigawa et al, 2008). The treatment of SAPHO syndrome remains empirical.…”
Section: Discussionmentioning
confidence: 99%
“…The etiologies that have been considered are infection of a joint or bone by a low-virulence pathogen such as Propionibacterium acnes, a reactive arthritis, or spondylitis [11]. Because of the frequency of sacroilitis, enthesopathies, inflammatory bowel disease, psoriasis, and the abundance of human leukocyte antigen-B27 (HLA-B27), SAPHO syndrome is considered a subtype of reactive spondyloarthropathy in seronegative spondylitis (SNSP) [12,13]. Diagnosing the syndrome is difficult, even with modern imaging techniques such as MRI or PET.…”
Section: Discussionmentioning
confidence: 99%